THE IMPACT OF SERVICE QUALITY, CUSTOMER PERCEIVED VALUE, AND BRAND EXPERIENCE ON LOYALTY WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLE (A Study on Lion Air Customers in Java) - Praditya, Avianto Dimas; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2018)
Customer Loyalty is an asset that must be maintained by the company. If a customer has a high degree of loyalty, then the costumer is more likely to use the service of the company again in the future. Lion Air is one of the largest airlines in Indonesia. However, Lion Air faced many problems such as the lack of punctuality and unsatisfactory of service. This study purpose is to analyze the impact of Service Quality, Customer Perceived Value, and Brand Experience on Loyalty with Customer Satisfaction as intervening.Data collection technique used in this study is non-probability sampling technique using purposive sampling with criteria Lion Air customer in Java Island who have used Lion Air service for at least twice in the past year. The number of sample collected were 168 respondents. To analyze the impact of independent variable on intervening variable and intervening variable to dependent variable, multi linear regression analysis was used.The result of this study showed that Service Quality have positive impact on Customersatisfaction (first hypothesis supported). Second hypothesis which state that Customer Perceived Value have positive impact on Customer Satisfaction is accepted as well. The third hypothesis which state that Brand Experience have positive impact on Customer Satisfaction is accepted. The coefficient of determination test result stated that all three variables have an impact of 88,9% on intervening variable. The fourth hypothesis which state that intervening variable Customer Satisfaction have positive impact on dependent variable Loyalty is accepted. The coefficient determination test result stated that intervening variable have an impact of 85,4% on dependent variable. Lion Airlines are recommended to develop their service, appearance, promotion, and punctuality.